2020
DOI: 10.1039/d0dt02529a
|View full text |Cite
|
Sign up to set email alerts
|

[4 + 2]-Cycloadditions of a thiazol-based tricyclic 1,4-diphosphinine and a new easy 1,4-diphosphinine protection deprotection strategy

Abstract: Diels–Alder-reactions of a thiazol-2-thione-based, tricyclic 1,4-diphosphinine were investigated, showing that the central aromatic π-system can react with various dienophiles. In one case, photochemical deprotection of the 1,4-diphosphinine was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 22 publications
1
13
1
Order By: Relevance
“…This showed that the formation of 1 a already occurs at ambient temperature and is completed after 16 hours, whereas temperatures higher than 120 °C for 48 hours are required for the generation of 1 b . The 31 P NMR shifts of δ =−107.9 ppm ( 1 a ) and δ=−92.5 ppm ( 1 b ) are in a typical range for 1,4‐diphosphabarrelenes [15,14,12] …”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…This showed that the formation of 1 a already occurs at ambient temperature and is completed after 16 hours, whereas temperatures higher than 120 °C for 48 hours are required for the generation of 1 b . The 31 P NMR shifts of δ =−107.9 ppm ( 1 a ) and δ=−92.5 ppm ( 1 b ) are in a typical range for 1,4‐diphosphabarrelenes [15,14,12] …”
Section: Resultsmentioning
confidence: 96%
“…The 31 P NMR shifts of δ = À 107.9 ppm (1 a) and δ = À 92.5 ppm (1 b) are in a typical range for 1,4-diphosphabarrelenes. [15,14,12] To evaluate the electronic properties of the new pyrrolyl phosphines, we determined the Tolman electronic parameter [22] (TEP) of 1 b by IR spectroscopic analysis of the corresponding nickel tricarbonyl complex [(CO) 3 Ni(μÀ 1 b)Ni(CO) 3 ] (2 b) (see SI for SCXRD study). With a TEP value of 2069.7 cm À 1 the electron donor ability of 1 b falls in the typical range of aryl phosphines (Table 1), yet the value is increased by 10 cm À 1 compared to the structural related bis(1,2,5-trimethylpyrrolyl)phenylphosphine (P(tmp) 2 Ph).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…26,27 Only recently dinuclear transition metal complexes of a nitrogen-bridged bent bis(NHC) have been published as first example of a heteroatom-bridged bent bis(NHC) ligand. 28 The observation that tricyclic 1,4-diphosphinines, related to III, 27,29 can undergo [4 + 2] cycloaddition reactions to form 1,4-diphosphabarrelenes 30,31 could be ideal starting points for a systematic study of phosphorus-bridged rigid, bent bis(NHC) chemistry, and it should be noted that closely related phosphabarrelenes have recently gathered attention as ligands in catalytic applications. 32 Historically, the first report of 1,4-diphosphabarrelenes came from Krespan in 1961, 33 a few more examples were published in the following years, 34,35 until Dielmann recently synthesised pyrrole-based 1,4-diphosphabarrelenes and metal complexes thus expanding the field of rigid, caged diphosphane ligands.…”
Section: Introductionmentioning
confidence: 99%